The Medical Institutional Repositories in Libraries (MIRL) Symposium: a blueprint designed in response to a community of practice need - Fay, Brenda; Buda, Lisa M.; Dellureficio, Anthony J.; Hoover, Sara; Kubilius, Ramune; Moore, Steven J.; Palmer, Lisa A. (Journal of the Medical Library Association, 2023)
Background: Health sciences libraries in medical schools, academic health centers, health care networks, and hospitals have established institutional repositories (IRs) to showcase their research achievements, increase visibility, expand the reach of institutional scholarship, and disseminate unique content. Newer roles for IRs include publishing open access journals, tracking researcher productivity, and serving as repositories for data sharing. Many repository managers oversee their IR with limited assistance from others at their institution. Therefore, IR practitioners find it valuable to network and learn from colleagues at other institutions. Case Presentation: This case report describes the genesis and implementation of a new initiative specifically designed for a health sciences audience: the Medical Institutional Repositories in Libraries (MIRL) Symposium. Six medical librarians from hospitals and academic institutions in the U.S. organized the inaugural symposium held virtually in November 2021. The goal was to fill a perceived gap in conference programming for IR practitioners in health settings. Themes of the 2021 and subsequent 2022 symposium included IR management, increasing readership and engagement, and platform migration. Post-symposium surveys were completed by 73/238 attendees (31%) in 2021 and by 62/180 (34%) in 2022. Feedback was overwhelmingly positive. Discussion: Participant responses in post-symposium surveys rated MIRL highly. The MIRL planning group intends to continue the symposium and hopes MIRL will steadily evolve, build community among IR practitioners in the health sciences, and expand the conversation around best practices for digital archiving of institutional content. The implementation design of MIRL serves as a blueprint for collaboratively bringing together a professional community of practice.